Low Prolactin Levels Identify HSDD and a Low Inhibition Profile in Women with Sexual Symptoms. (1st August 2022) - Maseroli, E; Verde, N; Cipriani, S; Fralassi, N; Alfaroli, C; Costeniero, D; Maggi, M; Auriemma, R; Vignozzi, L
ABSTRACT: Introduction: Data on the role of prolactin (PRL) in the physiologic range in the female sexual response are scanty. Objective: We aimed at investigating the association between PRL levels and sexual function, and specifically, with the desire domain as assessed by the Female Sexual Function Index. We also explored the presence of a cut-off level of PRL able to identify women with a diagnosis of Hypoactive Sexual Desire Disorder (HSDD). Methods: N=234 pre- and post-menopausal women (mean age 45.2+-12.4 years) consulting for female sexual dysfunction (FSD), and sexually active in the previous 4 weeks, were retrospectively analysed. A clinical, biochemical and pharmacological evaluation was performed. All patients completed the FSFI, the Female Sexual Distress Scale-Revised (FSDS-R), the Middlesex Hospital Questionnaire (MHQ) for the screening of psychopathological symptoms and the Sexual excitation/sexual inhibition scale (SIS/SES). Biochemical assessment included PRL (by luminescent oxygen channeling immunoassay). Results: Only few patients (n=9) had hyperPRL (PRL> 483.0 mU/L) and showed a significantly higher MHQ total score (p=0.043), lower Total (p=0.037), Desire (p=0.002), Arousal (p=0.024) and Satisfaction (p=0.026) FSFI scores and a higher FSDS-R score (p=0.006) compared with women with normoPRL women. At univariate linear regression analysis, we did not find a significant correlation between FSFI total score and PRL levels. Hypothesizing the non-linearity of the association between these 2 variables, we tested different fitting models and found that the quadratic relationship was the best fitting (R2=0.11).When stratifying normoPRL women into tertiles (T1: PRL < 163.55 mU/L; T2= PRL > 163.55 and < 262.0 mU/L; T3: PRL > 262.0 and < 483.0 mU/L), a significant difference emerged in FSFI Desire (p=0.001), Arousal (p=0.033) and Satisfaction (p=0.019) among the 4 groups; however, only the difference in Desire was confirmed (p=0.034) in a multivariate model. A post-hoc analysis showed that only women in the T3 PRL tertile had significantly higher scores in FSFI Desire (p=0.011) and Satisfaction (0.045) vs. women with hyperPRL.After excluding hyperPRL women, we compared PRL between women with (n=35) and without HSDD (n=190) and observed that those with HSDD showed significantly lower PRL levels (p=0.002). ROC curve analysis for PRL levels showed an accuracy of 0.615 +- 0.022, p = 0.040, in predicting HSDD, and when a threshold of PRL<190 mU/L was chosen, sensitivity and specificity for HSDD were both 64.7%. Finally, we compared women with PRL levels > and < 190 mU/L. At multivariate analysis, women with PRL <190 mU/L showed a significantly lower cortisol (p=0.017) and SIS1 score (p=0.049), a scale of sexual inhibition, than women with PRL >190 mU/L (bit still in the normal range). Conclusions: FSD women with hyperPRL showed a worse sexual function than those with normal PRL levels. However, when stratifying normoPRL women based on PRL tertiles, those included in the highest group had the best FSFI profile. Measuring PRL level in women with FSD is important, not only in order to ascertain the presence of a hyperPRL condition, but also to potentially predict the presence of HSDD or of a lower sexual inhibitory trait. Disclosure: No